LA GRAVITACION COMO UN MODELO DE CUERDA Y SU CUANTIZACION EN EL ESPACIO DE MINKOWSKI - Villegas Silva, Fulgencio (2006)
The gravitational field equations of Einstein are considered, identifying them with the function that describe to the immersion of the space-time at a flat space finding a model of field theory. Hilbert’s Lagrangian is used in such a way that dynamics fields measure the curvature of the space- time where the energy-momentum tensor is proportional to the Einstein’s tensor.